Rapid visual detection of Enterocytozoon hepatopenaei by recombinase polymerase amplification combined with lateral flow dipstick - Pang, Jianhu; Zhao, Caiyuan; Su, Hualong; Liu, Zhongcheng; Lu, Qiang; He, Xinyi; Weng, Shaoping; He, Jianguo (Frontiers in Marine Science, 2022)
Enterocytozoon hepatopenaei (EHP) is a high-impact pathogen in shrimp farming, causing huge economic losses to the global shrimp farming industry every year. However, current EHP detection methods are primarily based on the development of polymerase chain reaction (PCR) techniques that rely on sophisticated and expensive instruments. Consequently, a rapid, practical, and sensitive protocol for the detection of EHP is necessary. Recombinase polymerase amplification combined with a lateral flow dipstick (LFD-RPA) assay was developed using a pair of primers and nfo-probe targeting the conserved region of the spore wall protein gene. Under optimized reaction conditions, the LFD-RPA assay can detect 10 copies/μL of standard plasmid within 20 min at 40°C. Furthermore, the specificity of the LFD-RPA was also verified with other common pathogens of shrimp. Thirty-nine samples of Litopenaeus vannamei were collected in shrimp farms and detected using LFD-RPA and nested PCR. Thirty-two positive samples were detected by LFD-RPA. Compared with those of nested PCR, the diagnostic sensitivity and specificity of LFD-RPA were 100% and 100%, respectively. These results indicated the great application potential of the newly developed LFD-RPA assay for point-of-care diagnosis, epidemic surveillance, and epidemiological investigation of EHP.